A Selection of Source Opinions about the Relations between Crusaders and Byzantium during the First and Second Crusade - Bartosiewicz, Rafał (Vade Nobiscum, tom XXIV/2024: Studia nad Bliskim Wschodem, 2024)
Crusades pose a still vividly discussed topic in the area of research. In the public opinion dominates a belief, which has some reflection in the scientific literature, that the entire responsibility for ruining relations between the West and the Byzantium, which led to the fall of Constantinople in the year 1204, falls on the crusaders. A goal of this article is to verify these kinds of beliefs and to reflect on the political, cultural, religious, mental and military aspects of Byzantium’s relations with members of the First and Second Crusade. An analysis of these issues allows to make a profit and loss account of bilateral relations as well as to find structural problems, which hindered a mutual understanding.